Evaluating the effectiveness of Uganda's Supranational TB Reference Laboratory quality management system training program - Nakiwala Dorothy; Benjamini Niringiyimana; Wekiya Enock; Ocung Guido; Kabugo Joel; Adam Isa; Anita Katuramu; Orena Beatrice; Christine Nansubuga Korsah; Lillian Kyomugasho; Denis Oola; Kenneth Musisi; et al. (BMC, 2023)
Abstract Background Achieving the targeted organizational goals through effective training can increase employee satisfaction. Since 2015, the Supranational Reference Laboratory Uganda (SRL Uganda) has trained National Tuberculosis Reference Laboratories (NTRLs) from 21 countries in a variety of areas that cover both technical and programmatic aspects pertinent to TB laboratories. The Laboratory Quality Management System (LQMS) under SRL coordinates actions intended to ensure sustained quality of the laboratory services offered by the National TB Reference Laboratories. In order for laboratory results to be helpful in a clinical or public health setting, they must be accurate, reliable, and timely. The LQMS course aims to provide learners with knowledge on how to attain and maintain this quality. Prior to this study, there was hardly any data available on the effectiveness of LQMS trainings provided by SRL Uganda; using Kirkpatrick model, which is popular among researchers for evaluating the efficacy of the training program, this paper seeks to establish the effectiveness of the LQMS training offered by the SRL Uganda. Method We evaluated the effectiveness of LQMS training within the Uganda's SRL network for courses offered during the period 2017 and 2021 for participants from the Southern and East African sub-Saharan region. Results In 2017 and 2021, respectively, test results from 10/17 and 9/17 showed overall post-test scores above 80%. Of the 18 labs evaluated, 14 showed improvement; of these, 7 labs were from the Eastern region and the other 7 were from Southern Africa; one facility in this region also maintained its accreditation. In the post-evaluation assessment, attendees of the LQMS course gave feedback of strongly agree and agree variety. Conclusion More SRL Uganda network laboratories in the regions achieved a 5-star SLIPTA level rating and among these, 5 NTRLs got ISO 15189:2012 accredited by the end of 2021, while one maintained its accreditation status. This proves that the Laboratory Quality Management System training program was an effective tool in improving the quality of laboratory services, work practices, and processes.